2016
DOI: 10.5530/pc.2016.1.3
|View full text |Cite
|
Sign up to set email alerts
|

GC-MS Analysis of Frankincense Extracts which Inhibit the Growth of Bacterial Triggers of Selected Autoimmune Diseases

Abstract: Introduction: Frankincense has been used traditionally for the inhibition of microbial growth and for the treatment of rheumatic diseases. Despite this, frankincense extracts are yet to be tested for the ability to inhibit the growth of the bacterial triggers of autoimmune inflammatory diseases. Methods: Solvent extracts prepared from commercially obtained frankincense were analysed for the ability to inhibit the growth of bacterial species associated with initiating rheumatoid arthritis (P. mirabilis), ankylo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 33 publications
(23 reference statements)
1
15
0
Order By: Relevance
“…Indeed, previous studies from our group have also shown the low susceptibility of these P. aeruginosa strains to conventional antibiotics. 35,36 The methanolic and ethyl acetate extracts also inhibited P. aeruginosa growth, albeit with substantially smaller zones of inhibition (6.0 ± 0 and 6.7 ± 0.3 mm, respectively). The antimicrobial efficacy was further quantified by determining the MIC values for each extract against the microbial species which were determined to be susceptible.…”
Section: Antimicrobial Activitymentioning
confidence: 95%
See 1 more Smart Citation
“…Indeed, previous studies from our group have also shown the low susceptibility of these P. aeruginosa strains to conventional antibiotics. 35,36 The methanolic and ethyl acetate extracts also inhibited P. aeruginosa growth, albeit with substantially smaller zones of inhibition (6.0 ± 0 and 6.7 ± 0.3 mm, respectively). The antimicrobial efficacy was further quantified by determining the MIC values for each extract against the microbial species which were determined to be susceptible.…”
Section: Antimicrobial Activitymentioning
confidence: 95%
“…35,36 The system was equipped with a Shimadzu auto-sampler AOC-5000 plus (USA) fitted with a solid phase micro-extraction fibre (SPME) handling system utilising a Supelco (USA) divinely benzene/carbowax/polydimethylsiloxane (DVB/CAR/ PDMS). Chromatographic separation was accomplished using a 5% phenyl, 95% dimethylpolysiloxane (30 m×0.25 mm id×0.25 um) capillary column (Restek USA).…”
Section: Non-targeted Gc-ms Head Space Analysismentioning
confidence: 99%
“…This finding is supported by previous studies which have also reported these strains to be antibiotic resistant. 24,47 Thus, the K. senegalensis extracts are particularly potent growth inhibitors and may be useful for the inhibition of P. aeruginosa growth. Therefore, as both A. baylyi and P. aeruginosa can trigger multiple sclerosis in genetically susceptible individuals, 44 these extracts have potential in the prevention and treatment of this disease.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…27 Briefly, the system was equipped with a Shimadzu auto-sampler AOC-5000 plus (USA) fitted with a solid phase micro-extraction fibre (SPME) handling system utilising a Supelco (USA) divinyl benzene/ carbowax/polydimethylsiloxane (DVB/CAR/PDMS). Chromatographic separation was accomplished using a 5% pheny l, 95% dimethylpolysiloxane (30 m×0.25 mm id×0.25 µm) capillary column (Restek USA).…”
Section: Non-targeted Gc-ms Head Space Analysismentioning
confidence: 99%
“…This finding is supported by previous studies which have also reported these strains to be antibiotic resistant. 23,27 Thus, despite the relatively small inhibition zones, the T. lanceolata extracts may still be useful for the inhibition of P. aeruginosa growth. Therefore, as both A. baylyi and P. aeruginosa can trigger multiple sclerosis in genetically susceptible individuals, 28,29 these extracts have potential in the prevention and treatment of this disease.…”
Section: 11mentioning
confidence: 99%